Duration of immunity to SARS-CoV-2 in children after natural infection or vaccination in the omicron and pre-omicron era: A systematic review of clinical and immunological studies - Buonsenso, Danilo; Cusenza, Francesca; Passadore, Lucrezia; Bonanno, Francesca; De Guido, Claudia; Esposito, Susanna (Frontiers in immunology, 2023)
Duration of humoral and cellular memory in children previously infected SARS-CoV-2 or vaccinated and subsequent risk of reinfection is still not fully elucidated. Systematic review of studies retrieved from medical databases and article reference lists. From 2420 identified articles, 24 met the inclusion criteria. Children infected during the pre-omicron era developed long lasting (at least 10-12 months) humoral and cellular immunity against pre-Omicron SARS-CoV-2 variants, but have reduced cross-reactivity against Omicron. Conversely, although vaccination has a limited efficacy in preventing new infection with pre-Omicron and Omicron variants, studies suggested that vaccine-induced immunity provides better cross-neutralization against pre-Omicron and Omicron variants. Preprints published after the period of inclusion of our review suggested that overall risk of infection after Omicron infection is reduced, but children developed weak neutralizing responses in about half cases. Available evidence, although limited, suggested a long-lasting but unperfect protection of previous infections or vaccination against pre-Omicron and Omicron variants. Based on our findings, it might be reasonable to offer families of children infected before Omicron a booster vaccination. A similar indication should be proposed also for those infected with Omicron, specifically for more fragile children at higher risk of COVID-19-related complications, based on better cross-variant neutralisation induced by vaccination. PROSPERO, identifier ID 353189.